Sosialisasi dan Pengenalan Aplikasi Pengolahan Data SPSS pada Mahasiswa Administrasi Kesehatan Fakultas Ilmu Keolahragaan dan Kesehatan - Meliana Handayani; Yadi Jayadilaga; A. Ulfiana Fitri; Dian Anggraeni Rachman; Nurul Fajriah Istiqamah; Tenri Diah T.A; Adhinda Putri Pratiwi; Sri Rezkiani Kas (Institut Nalanda, 2023)
SPSS is a statistical data processing software or used for statistical analysis. SPSS is able to accommodate managing large data. Statistics has two very important main functions, descriptive and the inferential function. The purpose of implementing this activity is to optimize student potential in processing data that is appropriate and much needed in writing the final project. This activity was carried out at the Faculty of Sports Science, Makassar State University involving 177 participants, namely Health administration students. This activity is carried out in the form of socialization through explanations, providing tutorials or practice using SPSS as well as discussions. At the beginning of the activity students were asked to install the SPSS application, then explained and made tutorials and ended with data analysis. We thank those who have helped carry out this activity which can have a positive impact on the development of knowledge and soft skills in data processing by students.